Poster as an Information Product in the System of Scholarly Communications - A. S. Krymskaya (Библиосфера, 2024)
The poster session has become one of the types of professional events (congresses, conferences, seminars, etc.). Despite the long-term discussions about the poster as an effective tool in the scholarly communication and its comparison with the abstract it has not studied as a product of analytical and synthetic information processing. The purpose of this article is to consider theoretical questions about the poster as an information product. The traditional structure of the poster is similar to the structure of a research article (introduction, methods, results, discussion) with the only difference – the poster presents these elements in compressed form, as well as in an abstract. The article gives a comparative analysis of the poster and abstract. It shows that such features of the abstract as information content, high semantic capacity, accurate reflection of the main actual information and conclusions, etc., are characteristic of posters as well. It concludes that summarizing the results of the analytical and synthetic processing of information in the poster allows its considering as one of the types of information products and libraries can include posters in the list of their information products/services. In order to create posters, such skills as compression of information, data visualization, communicative skills, research skills and critical thinking, as well as mastering technical tools, which are in demand in the market today and are reflected in the professional standard “Specialist in Library and Information Activities”. Their development can be made by poster technology, which is already lately implemented at the Library and Information Department of the St. Petersburg State Institute of Culture.